Guimbal beach resorts as a leading tourist destination in Iloilo - Amoroso, Lorvilyn; Borbon, Maria Flor.; Latoza, Marjorie Luen.; Pangonotan, Josephine; Retamar, Jae Sance (2006.)
This research study aimed to determine if Guimbal beach resorts is the leading tourist destination in the province of Iloilo. It also aimed to know what factors are considered for the beach resorts in Guimbal to be attractive and be the best place for get together, recreation and relaxation. This study started on November and lasted on March of 2007. The subjects of the study were the 100 tourists within and outside the beaches of Guimbal. The dependent variable was the feasibility of Guimbal being the leading tourist destination in Iloilo. The demographic, socio-cultural, economic and political/legal factors were the independent variables. This research utilized a researcher-made questionnaire given to beach resort owners and 100 respondnets. The data gathered for this study were subjected to some computer-processed statistics such as, frequency distribution, mean score and chi-square set at .05 level of significance. All statistical computations were done using the Statistical package for Social Sciences (SPSS). The results of the study showed that only the location, amenities/facilities offered by the beach resorts, and the peace and order of Guimbal are the only factors that influenced the preferences of tourists in choosing Guimbal beach resorts as the leading tourist destination in Iloilo. Although the other factors identified did not directly affect their choice, these factors were still considered by the respondents in selecting their destination.
Research Paper (Mgt 199-Management Research). -- Iloilo City : University of the Philippines in the Visayas-College of Management, March 2006.